TINJAUAN YURIDIS TERHADAP HUBUNGAN ANTARA ALASAN MASYARAKAT DAN PERTIMABANGAN HAKIM DALAM MEMPERTIMBANGKAN DISPENSASI PERKAWINAN DI BAWAH - Sundari, Nata (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2023)
The problem of marriage dispensation in Indonesia is because on average the marriage dispensation application is granted by the judge in the religious court. in fact what happens if the dispensation is refused is the official appointed to grant the dispensation. This of course makes marriage dispensation more common in Indonesia. So that causes many practices of early marriage in Indonesia. The research method used is a qualitative research method with a sociological research approach. This type of research is a literature study in which the analysis is descriptive analysis linking the dispensation of marriage with certain norms. This research is to find out from the explanation of the background above so that this research is to find out how to build a juridical relationship between the reasons of the community and the judge's consideration in granting a marriage dispensation so that the judge can analyze the reasons and considerations of the judge in granting a marriage dispensation. analyze the reasons and considerations of judges in granting marriage dispensation. The results of this study are the reasons that form the basis of the first application. Influence of Customs, Habits and Religion, secondly Pregnancy out of wedlock, Economic Factors. In granting a request, consideration must be given to the juridical and sociological aspects and must also be based on the principles of the supreme court regulation Number 5 of 2019 concerning Guidelines for Trialing Applications for Dispensation of Marriage. In addition, the reasons of the applicant become the basis of the judge's balance to grant the marriage dispensation. This is for the benefit of potential defenders who are underage